Perancangan Mesin Abstrak Finite State Automata Untuk Aplikasi Sewa Tanah Desa - Sany, Diny Syarifah; Suwandi, Suwandi (Jurnal Teknologi Terpadu, 2022)
Village land rental is a government program with specific provisions to maximize the benefits of village assets. A village land rental application can be developed to facilitate village land rental activities, but there is no appropriate design model to build this type of application. The design model for village land rental applications can make it easier for developers to create land rental applications. Applications resulting from the suitable land lease model will maximize the performance of village land rental activities. Finite state automata (FSA) is an abstract machine that can be used and implemented into programming languages. The proposed FSA model is adapted to the village land lease activities. Data collection for research materials was taken from Girijaya Village, Cianjur Regency. Testing this model is carried out in two ways: scenario testing comparing the results of the FSA and actual activities. The second test is by implementing the proposed FSA into the PHP programming language and then testing respondents' feedback to assess the proposed FSA's accuracy. In the first test, by comparing the results of the FSA with actual activities, it was found that the designed FSA was following actual activities. For feedback testing, a questionnaire was carried out with ten respondents getting a score of 4.7 or equivalent according to to tend to be very suitable to be used as a reference in developing village land rental applications.